Background Predation Risk and Learned Predator Recognition in Convict Cichlids: Does Risk Allocation Constrain Learning?. (14th September 2016) - Joyce, Brendan J.; Demers, Ebony E.; Ferrari, Maud C. O.; Chivers, Douglas P.; Brown, Grant E.
Abstract: Exposure to elevated levels of background predation risk is known to shape the behavioural response of prey organisms to known and unknown predation threats. However, less is known regarding the effects of background predation risk on predator recognition learning. Here, we test the potential effects of elevated background predation risk on the strength and retention of learned predator recognition in juvenile convict cichlids ( Amatitlania nigrofasciata ). In a series of laboratory trials, we exposed shoals of juvenile cichlids to conditions of elevated (vs. low) levels of background risk and then conditioned them to recognize a novel predator odour (rainbow trout, Oncorhynchus mykiss ). The results of our first experiment demonstrate that despite showing reduced response intensities during initial conditioning (due to risk allocation), conditioned cichlids from high vs. low background risk show similar intensities of learned recognition when tested 24 h post‐conditioning. Moreover, elevated levels of background risk induced a predator avoidance response among unconditioned cichlids (due to induced neophobia). Our second experiment demonstrates that while we find no difference in the strength of learning when tested 24 h post‐conditioning, retention of acquired recognition is enhanced among cichlids from the high background predation risk treatment. Together, our results highlight the complex interacting effects past experience plays in shaping the response to acute predation threats.